Perkembangan Olahraga Berkuda Memanah Di Pesantren Tahun 2015-2022 - Ramadhan, Affan; Sulasman; Agus Permana (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to analyze the development of horseback riding and archery at Pesantren Daarut Tauhiid, Bandung, during the period 2015–2022. The research employed historical methodology, consisting of four main stages: heuristics, criticism, interpretation, and historiography. The findings indicate that these sports programs have developed significantly through the provision of facilities, involvement of professional trainers, and integration into the pesantren’s regular activities, such as tournaments and inter-pesantren competitions. This growth has been supported by the commitment of the pesantren leadership, community participation, and student enthusiasm, despite challenges related to budget constraints, facility management, and limited trainers. The study concludes that the program has been successfully implemented despite these obstacles and recommends improving facilities and adopting similar initiatives in other pesantren to preserve Sunnah sports within Islamic education. Keywords: Archery, Daarut Tauhiid, Horseback Riding, Pesantren, Sunnah Sports.